Ecophysiology, activity, and diversity of microbial communities in areas disturbed by a mining dam collapse - Batista, Éder Rodrigues (2021)
Fundão dam collapse, in Mariana, Minas Gerais, irreversibly modified the landscape, impacting ecosystems and, mostly, biotic communities. Microbial communities are important regulators of ecosystems functioning and given their high sensitivity and rapid responses to environmental disturbances, these communities are useful tools for assessing environmental quality. This thesis assessed the microbial response to changes in edaphic properties in areas disturbed by Fundão dam tailings deposition. The Paper 1 evaluated changes in microbial ecophysiology and activity associated with tailings deposition impacts across Gualaxo do Norte River. Overall, tailings samples exhibited high values of pH, silt, and bulk density, but low values of clay, organic carbon (Corg), total nitrogen (Nt), bioavailable heavy metals, and moisture. Microbial biomass, enzymatic activities, and total microbial activity potential were generally low in the tailings compared to undisturbed reference soils. Enzymatic activity integration using different soil quality indices indicated a significant reduction in the degradative efficacy of the microbial communities in the tailings in all the studied sites. Paper 2 has investigated the changes in microbial-controlled carbon dynamics in response to organic substrate availability and enzymatic activity at two upper horizon depths (A1: 0-3 cm and A2: 10-13 cm) in areas under the influence of tailings of the Fundão dam. It was observed the lower microbial growth (microbial biomass) and higher losses of microbial C (high qCO2) were associated with decreases in both the availability of organic substrate and in enzymatic activity (GMean index). Basal respiration has increased with increasing enzyme activity only at A2. Reduction in enzyme activity was associated with a lower content of organic matter in tailings, suggesting important changes in the microbial C dynamics in impacted areas. In paper 3, a metagenomic approach was used to investigate the taxonomic and functional diversity of microbial communities in samples collected during the rainy season of 2017 and 2019. Only the alpha diversity of microbial community functions was influenced by the impact of tailings deposition. The taxonomic and functional compositions, however, were consistently altered with impact and between sampling periods in some cases. Indicator value analysis has identified a total of 792 genera distributed in 108 microbial classes associated with both impacted and reference areas. Of the 8162 functions annotated, 1433 were identified as functional indicators, 779 of which were characteristic of impacted areas and 654 of reference areas. Overall, the ecophysiology of microbial communities was sensitively altered by changes in physicochemical properties of tailings, with emphasis on pH, resource availability (i.e., Corg, Nt), silt percentage, and bulk density. Enzyme activity, in turn, was mainly inhibited by the presence of Se, Cr, Fe, and Ni, even at low concentrations. Also, changes in organic substrate availability and enzyme activity promote trade-offs at the community-level resource allocation with consequences for microbial C dynamics in mine tailings. Additionally, the changes observed in taxonomic diversity, even small, as well as in the abundance and functional diversity of microbial communities, have implications for microbial processes fundamental to the ecosystem restoration in the impacted areas.